Conocimientos y prácticas sobre formas de prevención its-Vih/Sida en estudiantes de I a II año de bachillerato del Instituto Tecnológico Mariano Samaniego de la ciudad de Cariamanga sección diurna periodo septiembre 2009 – febrero 2010 - Montero Jiménez, Diana Alexandra (2010)
Diseases take treatment but the produced ones as a virus, do not recover in a definitive way, since the causal agent remains in latent condition (state), being able to reappear cyclically, facilitating his(her, your) transmission. The investigation(research) " Knowledge and you practice on forms of ITS-VIH/SIDA's prevention in students of I the IIIrd year of baccalaureate of the Technological Institute Mariano Samaniego of Cariamanga's city diurnal section period September, 2009 - February, 2010 " It (He, She) had as general aim(lens) " Identify that knowledge on ITS/VIH-SIDA, has the students of the I the IIIrd YEAR of Baccalaureate of the Technological Institute Mariano Samaniego of Cariamanga's City period September 2009-In February, 2010. This study is descriptive of transverse court(cut), which universe it is constituted by 364 students who belong(concern) to 1 º to 3 º year of baccalaureate; of them 190 students as sample population like result of the application of the formula: n=N/(1(α^2 xN)). Of which there are 93 students of masculine sex and 97 women of feminine sex. Of this investigation(research) it was obtained as result; of 190 students participants in this investigation(research), 85.2 % recognizes one of the infections product of the sexual contact like it is the VIH-AIDS, they recount the equal one to know about other infections as(like): genital Herpes, Syphilis, genital Warts, 87.9 % like them to anticipate(prepare) by means of the utilization of the condom, results that do not show major difference between the population with regard to the sex; this level of knowledge can owe the involucramiento of the academy to him(you, them) with regard to the topic. On the other hand, 3.7 % does not know on ITS-VIH/SIDA; and 5.2 % of his(her, your) prevention; alarming results considering the above mentioned pandemic to be that the teen and young population as the OPS brings(reports) it " it(he, she) can affect any person without discrimination of sex, being the most vulnerable population the teenagers, the statistics of brought(reported) cases demonstrate that the probability of acquiring the VIH is major in this group, since on the adolescence hormonal changes experiment. " And our locality is not the meaning, to this one ads that 95 % does not know the sexual and reproductive rights. On having finished this work it(he, she) comes near to the following conclusions, that the students do not receive sufficient information brings over of the sexual and reproductive rights as one does not possess(does not rely on) strategies adapted to help to spread his(her, your) knowledge; for what recommends to him(you, them) to spread widely knowledge on the ITS-VIH/SIDA across forums, videoes it(he, she) confers, debates where there take part actively those who shape the Institution sharing his(her,your) knowledge and hereby to help to reduce the pandemic.